Repetitive Transcranial Magnetic Stimulation for Improving Cognitive Function in Patients With Mild Cognitive Impairment: A Systematic Review - Jiang, Lijuan; Cui, Huiru; Zhang, Caidi; Cao, Xinyi; Gu, Nannan; Zhu, Yikang; Wang, Jijun; Yang, Zhi; Li, Chunbo (Frontiers in Aging Neuroscience, 2021)
Background: Mild cognitive impairment (MCI) is an early stage of Alzheimer’s disease. Repetitive transcranial magnetic stimulation (rTMS) has been widely used in research into MCI. However, there is no reliable systematic evidence regarding the effects of rTMS on MCI. The aim of this review was to evaluate the efficacy and safety of rTMS for the treatment of MCI. Methods: A comprehensive literature search of nine electronic databases was performed to identify articles published in English or Chinese before June 20, 2019. The identified articles were screened, data were extracted, and the methodological quality of the included trials was assessed. The meta-analysis was performed using RevMan 5.3 software. We used the GRADE approach to rate the quality of the evidence. Results: Nine studies comprised 369 patients were included. The meta-analysis showed that rTMS may significantly improve global cognitive function (standardized mean difference (SMD) 2.09, 95% confidence interval (CI) 0.94 to 3.24, p = 0.0004, 7 studies, n = 296; low quality evidence) and memory (SMD 0.44, 95% CI 0.16 to 0.72, p = 0.002, 6 studies, n = 204; moderate quality evidence). However, there was no significant improvement in executive function & attention (p > 0.05). Subgroup analyses revealed that (1) rTMS targeting the left hemisphere significantly enhanced global cognitive function, while rTMS targeting the bilateral hemisphere significantly enhanced global cognitive function and memory function (2) high-frequency rTMS significantly enhanced global cognitive function and memory function (3) the effects of ≥20 times rTMS treatment could improve global cognitive function and memory function. There was no significant difference in dropout rate (p > 0.05) between the two groups. However, patients who received rTMS had a higher rate of mild adverse effects (risk ratio (RR) 2.03, 95% CI 1.16 to 3.52, p = 0.01, 7 studies, n = 317; moderate quality evidence). Conclusions: rTMS has a positive effect on improving global cognitive function and memory function in patients with MCI and has good acceptability and fewer adverse effects. Nevertheless, these results should be interpreted cautiously due to the limitations of the study.